LANGUAGE POLITENESS STRATEGY OF TEACHER VERBAL INTERACTION IN THE CLASSROOM AT THE 8th GRADE (SOCIOLINGUISTICS APPROACH) - Br Pane, Hanna Juni Artika; Pasaribu, Yessy Octaviana; Napitupulu, Fenty Debora (Dharmas Education Journal (DE_Journal), 2021)
This study aims to observe and analyzed the used of politeness strategies that occur in verbal interactions in the classroom in junior high schools. This study applies a descriptive qualitative research design to observe and analyze the politeness strategies used by teachers to students in their interactions. Participants in this study were one English teacher and 30 students. The data in this study were in the form of utterances containing politeness strategies. Data were taken from English lessons for 90 minutes through direct observation and analysis. The findings of the study showed that there were a total of 60 excerpts containing three politeness strategies: Blind on record Strategy, Positive politeness Strategy and Negative politeness Strategy. The most dominant is bold on record with 31 data.